Where conventional security control validation falls short when evaluating organisational threats. Issue 12 (December 2020) - Evangelakos, Gus
Abstract : Information security challenges seem to grow more difficult every year – and that state of affairs is unlikely to change any time soon. In addition to the uneven playing field that defenders inhabit (attackers need only be right once, while defenders must be right every time), external events have conspired to make modern information security a more difficult task.